Long noncoding RNA ZFAS1 suppresses chondrocytes apoptosis via miR-302d-3p/SMAD2 in osteoarthritis. Issue 4 (19th January 2021) - Li, Jian; Liu, Mingting; Li, Xianrang; Shi, Hui; Sun, Shui
ABSTRACT: Osteoarthritis (OA) seriously affects people's quality of life due to joint pain, stiffness, disability, and dyskinesia worldwide. Long noncoding RNA zinc finger antisense 1 (ZFAS1) is downregulated and tightly associated with proliferation, migration, apoptosis, and matrix synthesis of chondrocyte in OA. However, the molecular mechanisms of ZFAS1 in OA remain unknown. The expression correlation between ZFAS1, miR-302d-3p, and SMAD2 in OA tissues was analyzed by Pearson correlation analysis. ZFAS1 was a lower expression, and expedited proliferation and repressed apoptosis of chondrocytes. MiR-302d-3p was a direct target of ZFAS1. MiR-302d-3p hindered proliferation and facilitated apoptosis of chondrocytes. MiR-302d-3p partially reversed the effect of ZFAS1 on proliferation and apoptosis of chondrocytes. SMAD2 was positively regulated by the ZFAS1/miR-302d-3p. MiR-302d-3p-mediated proliferation and apoptosis were partly abrogated by targeting SMAD2. ZFAS1 promoted chondrocytes proliferation and repressed apoptosis possibly by regulating miR-302d-3p/SMAD2 axis, providing a potential target for OA treatment. Graphical Abstract: